KEBERTAHANAN BAHASA DAERAH DALAM KONTEKS KEBIJAKAN BAHASA NASIONAL INDONESIA: KASUS BAHASA BATAK - Rosmawaty Rosmawaty (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The purpose of this study was to describe the influence of Batak cultural values and religious practices for Batak language maintenance. The result of this qualitative study indicates that the influence of Batak cultural valaues and religious practices vary among Angkola/ Mandailing, Toba, Simalungun, Karo and Pakpak/Dairi.The language maintenance from those variations created a continuum in the implementation of Indonesian language as the national language especially in North Sumatra